2007
DOI: 10.1002/ijc.22704
|View full text |Cite
|
Sign up to set email alerts
|

PTHrP‐induced MCP‐1 production by human bone marrow endothelial cells and osteoblasts promotes osteoclast differentiation and prostate cancer cell proliferation and invasion in vitro

Abstract: Prostate cancer (PCa) preferentially metastasizes to bone resulting in osteoblastic lesions with underlying osteolytic activities. The mechanisms through which PCa cells promote osteolytic activities and subsequent osteoblastic bone formation remain poorly understood. Parathyroid hormone-related protein (PTHrP), produced by bone cells and PCa, binds to receptors on osteoblasts and stimulates bone formation and resorption. We have previously reported that MCP-1 acts as a paracrine and autocrine factor for PCa p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 46 publications
1
66
1
Order By: Relevance
“…CCL2/CCR2 may mediate a cascade of signaling events to enhance tumor malignancy. For example, MDA-MB-231 cells can induce osteoblast hFOB1.19 and MC3T3-E1 to up-regulate CCL2 (57), and CCL2 produced by osteoblasts can promote osteoclast differentiation (47,48). Furthermore, tumor-derived CCL2 can exert function on other CCR2 ϩ stroma cells, such as endothelial cells (41) and mesenchymal stem cells (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CCL2/CCR2 may mediate a cascade of signaling events to enhance tumor malignancy. For example, MDA-MB-231 cells can induce osteoblast hFOB1.19 and MC3T3-E1 to up-regulate CCL2 (57), and CCL2 produced by osteoblasts can promote osteoclast differentiation (47,48). Furthermore, tumor-derived CCL2 can exert function on other CCR2 ϩ stroma cells, such as endothelial cells (41) and mesenchymal stem cells (21).…”
Section: Discussionmentioning
confidence: 99%
“…ous studies have shown that recombinant CCL2 protein can promote osteoclast fusion and differentiation in vitro (45)(46)(47)(48). Here, we wanted to test whether tumor cell-derived CCL2 could similarly elicit osteoclast activation and whether this is dependent on CCR2 expressed on osteoclast progenitor cells.…”
Section: Ccl2-overexpressing Tumor Cells Promote Osteoclast Differentmentioning
confidence: 99%
“…This bioactivity was not observed using the mid-region fragments, even those including NLS, nor using osteostatin, whose receptor has not yet been identified. (51) Therefore, because PTH-R1's binding by either PTH or PTHrP in PTH-R1-expressing cells of mesenchymal origin (such as OBs) leads to the activation of both RANKL and MCP-1 production, (43,52) we measured the production of these osteoclastogenic factors and their increase in the tumor microenvironment from malignant plasma cells, as reported. (53,54) We also measured MIP-1a as an additional pro-OC factor associated with hypercalcemia in MM.…”
Section: Discussionmentioning
confidence: 99%
“…sc-9680) recognizes full-length and NH 2 -terminal PTHrP (aa 1-34), whereas the rabbit anti-PTHrP (Calbiochem, Merck Chemicals Limited; cod. PC09) is specific for mid-region PTHrP (aa [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53]. Briefly, blotted polyvinyl difluoride (PVDF) membranes (Bio-Rad, Milan, Italy) were incubated with goat or rabbit anti-PTHrP and mouse anti-PTH-R1 mAbs (Santa Cruz Biotechnology), then with secondary antibodies and finally revealed by enhanced chemiluminescence (ECL Plus; GE Healthcare, Milan, Italy).…”
Section: Pthrp and Pth-r1 Proteinmentioning
confidence: 99%
“…CC motif ligand 2 (CCL2; aka monocyte chemoattractant protein-1 or MCP-1) is a potent chemotactic factor vital in the development and progression of PCa bone metastasis (4)(5)(6). CCL2 is a member of the CC subfamily of low molecular weight chemokines, a class of proteins that are essential in immune regulation, inflammation, and the healing response (7).…”
Section: Introductionmentioning
confidence: 99%